Overview of high‐risk Food and Drug Administration recalls for cosmetics and personal care products from 2002 to 2016. (22nd November 2018) - Janetos, Timothy M.; Akintilo, Lisa; Xu, Shuai
Summary: Background: There have been several recent controversies surrounding cosmetic products that have impacted health. Dermatologists are often the first to encounter these issues, and recalls are one metric of a safety profile of cosmetics and their impact on health. Objective: To analyze all recalls of cosmetic and personal care products from 2002 to 2016. Methods: This observational study describes all FDA cosmetic and personal care product recalls, acquired via a Freedom of Information Act request, from 2002 to 2016. The total number of Class I, Class II, and Class III recalls, number and origin of manufacturers, number of products affected, and main reason for recall were collected. Results: A total of 14 Class I, 266 Class II, and 33 Class III recalls were recorded. Baby products comprised the largest product category accounting for 24% of all recalls (76/313). 76% of recalls were due to bacterial contamination (237/313), followed by unapproved components, labeling issues, and skin irritation. The 14 Class I recalls accounted for 1.9 million products in distribution. Conclusions: Cosmetic recalls impacted millions of products and had the potential to cause serious harm. Dermatologists have the ability to strengthen public safety by reporting adverse events, encouraging recalls of harmful products, and lobbying through dermatology organizations for meaningful change to current cosmetic regulation.